Health-promoting behaviour of geriatric inmates in selected correctional facilities in south-west Nigeria - Olaoye, Samson Olukunmi (dialektika kontemporer, 2025)
In general, the ill health of elderly inmates can contribute to and represent an enormous burden of disease in society. In addition, if the elderly inmates do not have proper health-promoting habits, they will always suffer from health problems and this may shorten their lives in correctional institutions. Lack of health promoting habit of the geriatric inmates predisposes them to diseases and health problems especially mental problems. This can seriously strain available healthcare facilities and frustrate available resources that could have been directed in other productive directions. This study identified health-promoting habits of geriatric inmates in south-west Nigeria; examined the socioeconomic characteristics influencing the health behaviours of geriatric inmates in south-western Nigeria and; examined the challenges faced by geriatric inmates in their attempt to obtain health care in the selected correctional facilities in the study area. A cross-sectional study using questionnaire and in-depth-interview showed that geriatric inmates observed moment of rest, engaged in athletics, go for medical check-ups and eating balance diets as their health-promoting habits. Logistic regression showed influence of family support on health promoting habits of the geriatric inmates in the institution (OR: 2.046; P< 0.05; 95% CI1.053-3.976) and lack of fund for health care was the major challenge that geriatric inmates face in accessing health care in the institution. The paper concluded that health promoting-habits of the geriatric inmate were poor and this called for attention from government and correctional staff in Nigeria.